Brain-derived neurotrophic factor in obese women and its relationship with leptin and ghrelin - Kheirouri, Sorayya; Haghighi, Shirin; Saidpour, Atoosa (Progress in Nutrition, 2017)
Objectives: We aimed to assess the brain-derived neurotrophic factor (BDNF) level and its relation with leptin and ghrelin levels in obese women. Methods: In this case-control cross-sectional study, forty obese women and 40 healthy normal weight women aged (20- 50 y) were participated. Anthropometric indices were measured and serum levels of BDNF, leptin and ghrelin were assessed by the ELISA method. Results: Obese women had significantly higher leptin, but lower ghrelin levels compared with normal weight women. BDNF level was comparable between the two groups of women. There was a strong positive correlation between leptin and anthropometric parameters. A significant negative association was found between BDNF and leptin levels in normal weight women (r= -0.41, p= 0.02). Conclusion: Our results in women do not support a relationship between BDNF and obesity. Anthropometric indices may be important predictors of the leptin level. Further studies are required to elucidate the exact link between BDNF and leptin.